Clinical profile of meconium aspiration syndrome with special reference to birth weight, gestational age and immediate outcome at tertiary care centre - Chauhan, Anuya V.; Mahapatra, Sunita; Khare, Prarthana (International Journal of Contemporary Pediatrics, 2024)
Background: Meconium aspiration syndrome (MAS) is a leading cause of neonatal respiratory distress, occurring in 5% of infants born through meconium-stained amniotic fluid (MSAF). It is linked to fetal distress and can lead to significant lung complications. Methods: A prospective study was conducted from March 2021 to February 2022 in the NICU at Civil Hospital, Ahmedabad. MAS was diagnosed based on respiratory distress in neonates born through MSAF using criteria mentioned in Cloherty and Stark’s manual of neonatal care. The clinical and demographic information was recorded on pre-structured proforma & they were categorized into mild, moderate and severe MAS according to fraction of inspired oxygen (fiO2), duration of oxygen required and associated complications. Results: Among 110 neonates with MAS, 87% were full-term, 11% post-term, and none preterm. Most (49.09%) weighed between 2.50–2.99 kg, and 85.45% were appropriate for gestational age. Severe birth asphyxia was the most common comorbidity (30.90%), followed by septicemia and pneumothorax. HFNC was used in 57.27% of cases, while 32.72% required ventilation. The mortality rate was 10%, with pneumothorax being the leading cause of death. Conclusion: Proper antenatal care with prevention and treatment of maternal risk factors, intrapartum assessment of foetal distress and use of proper aseptic techniques during delivery & resuscitation and then transport of the baby to referral centre help in reducing morbidity and mortality in MAS neonates. After birth, timely diagnosis and provision of proper respiratory support by assessment of the severity of distress can prevent the mortality and morbidity due to MAS.